Materiais usados como pigmento no período colonial brasileiro - Cianciarulo, Adriana Quilici Barreto (2014)
Based on the history of science, this research aimed to discover the materials used as pigment and the specificities of colonial Brazilian artistic production through literature related to decorative arts of the period. To achieve some of those materials we‟ve referred the treatises on painting of the italians Cennino Cennini‟s Trattato della Pittura (c. 1398) and Giorgio Vasari‟s Le Vite de più eccelenti architetti, pittori, et scultori italiani, da Cimabue, insino a tempi nostril (1550); of the portugueses Filipe Nunes‟s Arte da Pintura, Symetria e Perspectiva (1615); as well as the dictionary of terms of Rafael Bluteau‟s Vocabulario Portuguez e Latino (1712) and the text Segredos necessarios para os officios, artes e manufacturas, e para muitos objectos sobre a economia domestica (1794). We also observed artistic knowledge present in some of the books published by the Casa Literária do Arco do Cego and partner publishers (1799 to 1801). Several elements to the composition of this research came from contemporary studies in the areas of architecture and conservation restoration related to Jesuit constructions of art and colonial painting and scientific analyses of these materials